A calorimetric characterization of the interaction of quinacrine with poly(I).poly(C) and its comparison to proflavine. (April 2019) - Basu, Anirban; Suresh Kumar, Gopinatha
Highlights: Energetics of the binding of quinacrine and proflavine with poly(I).poly(C) was studied. The binding was exothermic in both the cases. Enthalpy-entropy compensation and negative heat capacity value was observed in both the cases. The binding was driven largely by non-polylectrolytic forces for both quinacrine and proflavine. Abstract: Thermodynamics of the interaction of quinacrine with poly(I).poly(C) was studied in comparison to proflavine using microcalorimetry. Isothermal titration calorimetry results suggested that the binding of quinacrine to poly(I).poly(C) was enthalpy dominated with a smaller but favourable entropic contribution at 298.15 K. For proflavine, the binding was predominantly entropy dominated at 298.15 K. The equilibrium constant for quinacrine-poly(I).poly(C) complexation was calculated to be (5.11 ± 0.88)·10 5 M −1 while for proflavine the equilibrium constant was (3.45 ± 0.85)·10 5 M −1 at 298.15 K. With increasing temperature the equilibrium constant decreased, the standard molar enthalpic contribution increased in magnitude, the positive standard molar entropic contribution decreased while standard molar Gibbs energy remained almost invariant for both the systems. An enthalpy-entropy compensation phenomenon was observed for the complexation of both quinacrine and proflavine with poly(I).poly(C). Negative standard molar heat capacity values were also observed for the complexation of both quinacrine and proflavine with poly(I).poly(C) which suggested the involvement of hydrophobic forces in the binding reaction. Salt dependent calorimetric data and the dissection of the standard molar Gibbs energy suggested the involvement of a dominant non-electrostatic component in the binding reaction for both quinacrine and proflavine.